Migration and housing price effects of place-based college scholarships - Timothy J. Bartik; Nathan Sotherland (W.E. Upjohn Institute for Employment Research, 2015)
Place-based college scholarships, such as the Kalamazoo Promise, provide students who live in a particular place, and/or who attend a particular school district, with generous college scholarships. An important potential benefit from such "Promise programs" is their short-term effects on local economic development. Generous Promise scholarships provide an incentive for families to locate in a particular place, which may change migration patterns, and potentially boost local employment and housing prices. Using data from the American Community Survey, this paper estimates the average effects of eight relatively generous Promise programs on migration rates and housing prices in their local labor market. The paper finds evidence that Promise programs lead to significantly reduced out-migration rates for at least three years after a Promise program is announced. These reductions in out-migration rates are larger for households with children, and are also larger when we focus on smaller areas around the Promise-eligible zone rather than the entire local labor market. These out-migration effects are large, implying that Promise programs lead to a 1.7% increase in overall population of the local labor market.
Keywords: I22; I25; I28; J61; R23; 330; college scholarships; Kalamazoo Promise; local economic development; migration